Criteria for Class F contractor selection for maintenance work / Mohd Kamarul Hisam Muhammad - Muhammad, Mohd Kamarul Hisam (2006)
One of the most critical problems of bidding process is contractor selection. There is a need to develop a mechanism to determine client's requirements in selecting contractor. Therefore, the aim of this research is to analyze the data collected from a survey on clients to study the major factors influencing client requirement in construction industry, over thirty client in four districts at Perak state and two hundred and thirty five contractors were involved in this research. The objectives of this research are p identify the problem/ issues on selecting contractor including establishing the client's requirements and to win the bidding process. Through there analysis, it can be concluded that all the client requirements identified are so important to the contractor in order to increase their chances to win the bid. Contractors must have a good effort on how to upgrade their performance in construction industry to realize what client needs.